Computational fluid dynamic analysis of calcified coronary plaques: Correlation between hemodynamic changes and cardiac image analysis based on left coronary bifurcation angle and lumen assessments - Sun, Zhonghua; Chaichana, T. (Future Medicine Ltd, 2016)
The purpose of this study was to determine the relationship between left coronary bifurcation angle and significant coronary stenosis with use of coronary CT angiography (CCTA)-generated computational fluid dynamics (CFD) analysis when compared to the CCTA analysis of coronary lumen stenosis with invasive coronary angiography (ICA) as the reference method. Eleven patients with calcified plaques at the left coronary artery tree who underwent CCTA and ICA examinations were included in the study. CFD simulation of left coronary models was performed to analyse hemodynamic changes including wall shear stress, wall pressure and flow velocity. The mean bifurcation angle was measured 83.3 ± 17.1° and 83.3 ± 17.0° on CCTA and ICA, respectively, with no significant difference (p=0.99). Of 15 significant stenosis at left anterior descending (LAD) and left circumflex (LCx) on CCTA, only 3 of them were confirmed to be > 50% stenosis on ICA. Wall shear stress was noted to increase in the LAD and LCx models with significant stenosis and wider angulation (> 80°), but remained no change in most of the other coronary models with no significant stenosis and narrower angulation. Wall pressured was decreased at the significant stenotic lesions, while flow velocity was increased with flow turbulence at the post-stenotic sites. This study further clarifies the direct correlation between left coronary bifurcation angle and significant stenosis, with angulation measurement being more accurate than lumen assessment for diagnosing significant stenosis.